2016
DOI: 10.1111/eva.12430
|View full text |Cite
|
Sign up to set email alerts
|

Sockeye salmon repatriation leads to population re‐establishment and rapid introgression with native kokanee

Abstract: Re‐establishing salmonid populations to areas historically occupied has the substantial potential for conservation gains; however, such interventions also risk negatively impacting native resident stocks. Here, we assessed the success of the hatchery‐assisted reintroduction of anadromous sockeye salmon (Oncorhynchus nerka) into Skaha Lake, British Columbia, Canada, and evaluated the genetic consequences for native kokanee, a freshwater‐obligate ecotype, using single nucleotide polymorphism genotypic data colle… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5
1
1

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(47 citation statements)
references
References 57 publications
0
47
0
Order By: Relevance
“…29 15Shuswap LakeEagle RiverBritish Columbia, CanadaFraserKokaneeStream90.28Taylor et al . 29 16Skaha LakeOkanagan RiverBritish Columbia, CanadaColumbiaSockeyeStream330.02Veale & Russello 71 17Penticton ChannelBritish Columbia, CanadaColumbiaKokaneeStream190.08Veale & Russello 71 18Okanagan LakeOkanagan LakeBritish Columbia, CanadaColumbiaKokaneeShore1440.99Lemay & Russello 59 Mission CreekBritish Columbia, CanadaColumbiaKokaneeStream1360.10Lemay & Russello 59 19Wood LakeWood LakeBritish Columbia, CanadaColumbiaKokaneeShore480.92Frazer & Russello 42 Middle Vernon CreekBritish Columbia, CanadaColumbiaKokaneeStream480.28Frazer & Russello 42 20Kalmalka LakeKalmalka LakeBritish Columbia, CanadaColumbiaKokaneeShore320.95Veale & Russello 71 Coldstream CreekBritish Columbia, CanadaColumbiaKokaneeStream320.23Veale & Russello 71 21Christina LakeChristina LakeBritish Columbia, CanadaColumbiaKokaneeShore481.00Frazer 70 Sanders CreekBritish Columbia, CanadaColumbiaKokaneeStream480.07Frazer 70 22…”
Section: Resultsmentioning
confidence: 99%
“…29 15Shuswap LakeEagle RiverBritish Columbia, CanadaFraserKokaneeStream90.28Taylor et al . 29 16Skaha LakeOkanagan RiverBritish Columbia, CanadaColumbiaSockeyeStream330.02Veale & Russello 71 17Penticton ChannelBritish Columbia, CanadaColumbiaKokaneeStream190.08Veale & Russello 71 18Okanagan LakeOkanagan LakeBritish Columbia, CanadaColumbiaKokaneeShore1440.99Lemay & Russello 59 Mission CreekBritish Columbia, CanadaColumbiaKokaneeStream1360.10Lemay & Russello 59 19Wood LakeWood LakeBritish Columbia, CanadaColumbiaKokaneeShore480.92Frazer & Russello 42 Middle Vernon CreekBritish Columbia, CanadaColumbiaKokaneeStream480.28Frazer & Russello 42 20Kalmalka LakeKalmalka LakeBritish Columbia, CanadaColumbiaKokaneeShore320.95Veale & Russello 71 Coldstream CreekBritish Columbia, CanadaColumbiaKokaneeStream320.23Veale & Russello 71 21Christina LakeChristina LakeBritish Columbia, CanadaColumbiaKokaneeShore481.00Frazer 70 Sanders CreekBritish Columbia, CanadaColumbiaKokaneeStream480.07Frazer 70 22…”
Section: Resultsmentioning
confidence: 99%
“…Seaward migration of kokanee also has been observed in Skaha Lake, British Columbia (Richard Bussanich, Okanagan Nation Alliance, oral commun., January 5, 2017), where Sockeye Salmon were reintroduced. Interestingly, reintroduction of Sockeye Salmon into Skaha Lake has led to hybridization with kokanee (Veale and Russello, 2016). Veale and Russello (2016) reported that hybrids represented 15 percent of age-0 fish, were intermediate in size, and had reduced fitness for traits associated with anadromous and freshwater life histories.…”
Section: Chinook Salmon Donorsmentioning
confidence: 99%
“…Interestingly, reintroduction of Sockeye Salmon into Skaha Lake has led to hybridization with kokanee (Veale and Russello, 2016). Veale and Russello (2016) reported that hybrids represented 15 percent of age-0 fish, were intermediate in size, and had reduced fitness for traits associated with anadromous and freshwater life histories. Hybridization generally occurs through male kokanee associating with spawning Sockeye Salmon (Foote and Larkin, 1988).…”
Section: Chinook Salmon Donorsmentioning
confidence: 99%
“…In the case of kokanee, the application of population genomic techniques has allowed for the identification of outlier loci that are associated with reproductive ecotypes in a number of lakes throughout British Columbia and elsewhere across their distribution (Russello et al. ; Frazer and Russello ; Lemay and Russello ; Veale and Russello , , b). Importantly, the incorporation of outlier loci within genotyping panels has greatly improved the accuracy and precision of individual assignment and mixed‐composition analyses for management of kokanee (Lemay and Russello , ; Russello et al.…”
mentioning
confidence: 99%
“…Importantly, the incorporation of outlier loci within genotyping panels has greatly improved the accuracy and precision of individual assignment and mixed‐composition analyses for management of kokanee (Lemay and Russello , ; Russello et al. ; Frazer and Russello ; Veale and Russello ), and other freshwater and marine species (Freamo et al. ; Corander et al.…”
mentioning
confidence: 99%